2017
DOI: 10.1038/srep41803
|View full text |Cite
|
Sign up to set email alerts
|

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis

Abstract: Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…Given the recent implication of monoallelic MYH3 variants in some cases of SCTS 6,7 and the suspicion that recessive inheritance underpins SCTS in the families in this study, the maternally transmitted haplotypes in individuals 1 and 2 were also examined. This showed that the top maternally transmitted haplotype that individuals 1 and 2 shared with individual 5 was also inclusive of the MYH3 locus (a 9 cM segment encompassing 28 annotated genes; Figure 2B).…”
Section: Analysis Of Shared Haplotypesmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the recent implication of monoallelic MYH3 variants in some cases of SCTS 6,7 and the suspicion that recessive inheritance underpins SCTS in the families in this study, the maternally transmitted haplotypes in individuals 1 and 2 were also examined. This showed that the top maternally transmitted haplotype that individuals 1 and 2 shared with individual 5 was also inclusive of the MYH3 locus (a 9 cM segment encompassing 28 annotated genes; Figure 2B).…”
Section: Analysis Of Shared Haplotypesmentioning
confidence: 99%
“…The wider cohort of SCTS-affected individuals without pathogenic variants in FLNB (n ¼ 16) had significantly more MYH3 truncating variants than presumptively healthy control individuals from publicly available databases (Supplemental Data). In the Genome Aggregation Database (gnomAD), 13 Our observations that individuals 1, 2, and 5 carry the same MYH3 splice-site variant on a shared paternal haplotype and also share a maternal haplotype in the context of 6 Zieba et al 7 Chong et al sibling recurrence suggest that a maternally derived pathogenic variant remains to be defined. We therefore performed WGS on individuals 1-3 and then prioritized and filtered MYH3 variants for high impact (SnpEff).…”
Section: Analysis Of Shared Haplotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Mutations in MYH3, which encodes embryonic myosin heavy chain 3, have been detected in some families with autosomal dominant SCT. 3 However, in some cases, the specific genetic mutation remains unknown. 2 Our patient underwent genetic study, with testing for mutation of the FLNB gene, but no specific genetic mutation could be demonstrated.…”
mentioning
confidence: 99%